Estratégias de descontaminação para recuperação da resistência de união à dentina de um sistema adesivo universal após contaminação por saliva - Maia, Susana Joice Mendes (2024)
Adhesive systems are highly technique-sensitive, and achieving clinically acceptable interfaces depends on the correct application of the material and moisture control. Contamination during the adhesive procedure, whether by saliva, blood, or gingival fluids, is common and highly detrimental to the quality of the interface, potentially compromising the longevity of the restoration. This study aimed to evaluate and compare in vitro the effects of salivary contamination and decontamination procedures on the recovery of bond strength to dentin using a universal adhesive system in both etch-and-rinse and self-etch strategies, after contamination by saliva at different stages. The sample consisted of 114 extracted sound molars, randomly divided into 19 groups (n=6). In 12 of these groups, the universal adhesive (Single Bond Universal, 3M) was used in the etch-and-rinse strategy, and in the remaining 7 groups, the self- etch strategy was employed. The groups differed based on the timing of salivary contamination (after acid etching [C1], after adhesive application but before polymerization [C2 and CA1], and after adhesive polymerization [C3 and CA2]) and the decontamination procedures applied (Rinse + air drying [RA]; LS + re-etching [RE]; RA + reapplication of the adhesive [RA]; RA + RE + RA; RA + removal with a bur + RE + RA). The restored teeth with composite resin were stored in distilled water for 24 hours at 37ºC (immediate test) or for 6 months, then subjected to microtensile bond strength testing and fracture pattern analysis. Scanning electron microscopy (SEM) was conducted to analyze the interface of contaminated groups. Bond strength data were analyzed by two-way ANOVA followed by Tukey’s post-hoc test (p < 0.05). Overall, bond strength was maintained after 6 months (p > 0.05). In all evaluated stages (C1, C2, C3, CA1, and CA2), salivary contamination affected bond strength (p < 0.05), with the most critical stage being after adhesive application without polymerization (C2 and CA1). Decontamination with re-etching (RA + RE) was crucial for adhesion when contamination occurred after acid etching. All decontamination procedures restored bond strength to control levels in the self-etch strategy after 6 months. Thus, it can be concluded that at all stages of contamination, the universal adhesive system showed a reduction in bond strength (BS) after 24 hours or 6 months, with the most critical reduction occurring when the contamination was on the unpolymerized adhesive. In the etching and rinsing strategy, reapplying the acid when contamination occurred after etching, and rinsing and drying when contamination occurred on the unpolymerised adhesive, were not effective. for the self-etching strategy, all decontaminations recovered the BS. Furthermore, in all the groups evaluated, the BS was maintained after 6 months.